Family control and ownership monitoring in family-controlled firms in Japan - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2010)
This paper focuses on a type of firms that have been traditionally neglected in both family business and governance research, namely, family-controlled, publicly-listed firms. Although principal-agent conflicts may be less prevalent in such firms, family control can potentially give rise to principal-principal conflicts, leading to expropriation of the wealth of minority owners by family owners. Superior firm performance and the willingness to distribute the profits through dividend payments would suggest the absence of such expropriation. Based on a sample of 210 OTC firms in Japan, we examined the relationships between family control and dividend payouts and profitability. Our results indicate that family control was positively related to dividend payouts. Further, we found that while foreign ownership interacted with family control to reduce dividend payouts and increase profitability, bank ownership did not have such an effect.